Grain Sorghum Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2003)
This publication projects a budget that reflects expected income and costs based on typical production of grain sorghum in western Kansas.
MF904_2003_10
Keywords: MF904; Economics; Crops; MF